Notes on intersectional political economy: The long period method, technical change, and gender - Luiza Nassif Pires (Levy Economics Institute of Bard College, 2020)
This paper presents a critique of Karl Marx's labor theory of value and his theory of falling profit rates from an intersectional political economy perspective. Specifically, I rely on social reproduction theory to propose that Marx-biased technical change disrupts the social order and leads to competition between workers. The bargaining power of workers cannot be dissociated from class struggle within the working class. I argue that technical change increases social conflict, which can counterbalance the long-run tendency of the profit rate to fall. The conclusion is that class struggle is multilayered and endogenous to the process of accumulation.
Keywords: B54; B51; J51; O33; 330; Political Economy; Social Reproduction Theory; Gender and Racial Economics; Labor Unions; Technical Change